A high energy density Li2S@C nanocomposite cathode with a nitrogen-doped carbon nanotube top current collector1. Issue 37 (7th October 2015) - Zhang, Su; Liu, Meinan; Ma, Fei; Ye, Fangmin; Li, Hongfei; Zhang, Xinyi; Hou, Yuan; Qiu, Yongcai; Li, Wanfei; Wang, Jian; Wang, Jin; Zhang, Yuegang
<x xml:space="preserve">Abstract</x> High energy density lithium sulfur batteries with 804 Wh/kg were reported based on sheet-like Li2S@C composites with the assistance of nitrogen doped carbon nanotube film.